Voices in the Classroom: Unraveling the Impact of Teacher Beliefs on Speaking Skills - Halim, Abdul; Yang, Chen Ching; Nasril, Nasril (IAIN KENDARI, 2023)
Focusing on teacher beliefs in language instruction, this research explores their nuanced influence on speaking classes. By examining teacher reflections and students' experiences, the study reveals a multifaceted process wherein educators employ innovative techniques to foster critical thinking and active participation. The findings emphasize the transformative potential of teacher-student interactions, underscoring the importance of recognizing and leveraging these beliefs for more effective language instruction. Keywords: Teacher belief, Speaking skill, Reflective practice, Student centered-learning